Government budget forecasting : theory and practice - Sun, Jinping; Lynch, Thomas Dexter, 1942- (Boca Raton : CRC Press, 2008)
This book is particularly evident during times of finacial constraint, when citizens impose greater accountability upon government to use taxpayer dollars more efficiently.
Includes bibliographical references and index.
aug 06/06/13
Loans
Keywords: Local budgets -- United States -- States; Local finance -- United States -- States